Implementasi Algoritma Gunning Fog Index Untuk Mengukur Tingkat Keterbacaan Tugas Akhir Mahasiswa Menggunakan Pemrograman Python - Riza, Noviana; Supriady, Supriady; Setiadi, Hilman; Prianto, Cahyo (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This research is motivated by the importance of abstracts in a scientific work as a key element that provides an overview of the content of the research. Abstracts are a key element in scientific work, and their readability is important so that the research message can be well understood by readers. However, students' abilities in writing abstracts vary greatly. Some students still have difficulty in compiling abstracts that comply with the rules, which affects the readability and understanding of their research by readers. In addition, there are also students who are already proficient in making abstracts. Therefore, this study aims to measure the level of readability of students' final project abstracts and identify the factors that influence it using the Gunning Fog Index. This study involves the analysis of 100 abstracts from various departments at the University of Logistics and International Business. A web-based application will be built using Python. The model created will be implemented in the form of an application to make it easier for users to find out the level of readability. The implementation results show that the average Gunning Fog Index of the 100 abstracts analyzed was 9.2564, which means that the abstracts can generally be understood by readers with an education level equivalent to grade 9 of junior high school. The majority of abstracts (68%) were categorized as easy to read, while 9% were in the moderate category and 23% were difficult. The analysis also showed variations in readability levels between departments, with Study Program D having the highest average Gunning Fog Index and Study Program A having the lowest. Overall, this implementation successfully demonstrated the readability levels of students’ abstracts and provided insight into variations in writing quality between departments.